Micro, Small-Financial Financing and Its Implications on the Profitability of Sharia Banks - Aminah Nuriyah; Endri Endri; Mukhamad Yasid (Universitas Pelita Harapan, 2018)
Development of micro, small and medium enterprises (MSME) in Indonesia has increased yearly, but this is not followed by MSME financing in Sharia banking, where the proportion is relatively decreasing in a couple years. This study aims to analyze the influence of the deposit or third party fund to MSME financing and also to analyze the implication of MSME financing to MSME financing and its impact on the profitability of Sharia banks. Sharia banks are expected to be even more active in collecting funds from third parties with various strategies that can be used. As has been discovered from the above research, the amount of fund raising to the allocation of MSME financing is also getting bigger. This study uses a Vector Error Correction Model (VECM) to see the long term effect and response to shocks that occur in the studied variables. The result shows that in the short run and the long run CAR has negative and significant effect on MSME financing. TPF, NPF, BOPO and FDR have positive significant to MSME financing in the long term. TPF, CAR, NPF have positive significance to Sharia banks profitability in the long term. BOPO and NPF have positive significance in the short run. Shock to CAR is negatively responsed by MSME financing. Shock to MSME financing is negatively responsed by Sharia banks profitability (ROA) and is stable in the long term.Abstrak dalam Bahasa Indonesia : Perkembangan Usaha Mikro, Kecil dan Menengah (UMKM) di Indonesia meningkat setiap tahun, tetapi ini tidak diikuti oleh pembiayaan UKM di perbankan syariah, yang proporsinya relatif menurun dalam beberapa tahun. Penelitian ini bertujuan untuk menganalisis pengaruh Deposito atau dana pihak ketiga terhadap pembiayaan UMKM dan juga menganalisis implikasi dari Pembiayaan UMKM terhadap profitabilitas bank syariah. Bank-bank syariah diharapkan untuk lebih giat lagi dalam menghimpun dana dari pihak ketiga dengan berbagai strategi yang dapat digunakan. Seperti telah diketahui dari penelitian diatas yaitu jika jumlah penghimpunan dana semakin besar maka alokasi pembiayaan UMKM juga semakin besar. Penelitian ini menggunakan Vector Error Correction Model (VECM) untuk melihat efek jangka panjang dan respon terhadap shock yang terjadi pada variabel yang diteliti. Hasilnya menunjukkan bahwa dalam jangka pendek dan jangka panjang CAR memiliki pengaruh negatif dan signifikan terhadap Pembiayaan UMKM. TPF, NPF, BOPO dan FDR memiliki signifikan positif terhadap pembiayaan UMKM dalam jangka panjang. TPF, CAR, NPF memiliki signifikan positif terhadap profitabilitas bank sharia dalam jangka panjang. BOPO dan NPF memiliki signifikan positif dalam jangka pendek. Guncangan terhadap CAR direspon negatif oleh pembiayaan UMKM. Kekagetan terhadap pembiayaan UMKM secara negatif direspon oleh Profitabilitas Bank Syariah (ROA) dan akan stabil dalam jangka panjang.